Problem In Language Learning Advantages Of The Method Of Analysis (Journal of Pedagogical Inventions and Practices, 2024)
The principles of teaching students to work with texts in teaching other languages, that is, teaching a second language based on the method of problem analysis, is the main language unit of the teaching content. The goal of problem-based education is not only to master the results of scientific knowledge and the system of knowledge, but also to master the way to achieve the results of this process, to form the student's independent knowledge and to develop his creative abilities